Single Stage Knee Arthroplasty Revision Surgery: A Systematic Review of the Literature - Chew, E (Open Orthop J, 2015)
Total Knee Arthroplasty is an increasingly common procedure and revision surgery, particularly for infection, is associated with significant morbidity and healthcare costs. The current gold standard is a two stage revision procedure but single stage revision is increasingly being used in some departments to improve patient outcomes. We conducted a systematic review of the literature to determine the up-to-date evidence underlying the use of a single stage knee approach in revision surgery. A total of 12 studies were included in this review amounting to 433 revision surgeries. This is the largest review of single stage knee revision surgery. The procedures described were heterogenous and included the ‘two-in-one’ technique as well as other single stage revision procedures. There were also differences in implants and antibiotic regimens. The mean re-infection rates described in 10 studies was 9.4% (range 0-19.2%) after a mean follow-up of 40.3 months (range 7-180 months). The re-infection rates in the studies published over the last 30 years are falling, and this is not accounted for by any significant change in duration of follow-up during this period. The outcome scores varied, but patients generally showed an improvement. The Knee Society Score and the Oxford Knee Score were the most commonly used in five and three studies respectively. We conclude that the current evidence for single stage revision is variable and there is a lack of good quality evidence to address whether single stage revisions is thorough enough to eradicate deep infection and is able to restore adequate function. There is a need for larger prospective studies with standardised procedures and protocol, and with adequate follow-up. Till then, patients considered for a single stage approach should be thoroughly assessed and the surgery should be performed by a senior surgeon with experience in single stage knee revisions.